(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2017)
Introduction: In the background of resource limited setting like Nepal, we set out to identify if specific clinical characteristics and basic lab parameters would guide differentiation of Tuberculous from other causes of exudative pleural effusion. Methodology: Retrospective study of 109 consecutive patients with exudative pleural effusion. Results: Compared to Tubercular pleural effusions (41.3%), increased age, increased duration of symptom and increased pack years statistically favoured a diagnosis of Malignant pleural effusion(21.1%), whereas presence of fever, cough and increased pleural ADA levels favoured Tubercular pleural effusions. With regards to Parapneumonic effusions (26.6%), a shorter duration of symptom, smaller effusions, higher pleural Neutrophils, lower pleural lymphocyte neutrophil ratio and lower ADA favoured the diagnosis as compared to Tubercular pleural effusions. Conclusions: The appreciation of important clinical and pleural biochemical differences between Tubercular and other major causes of exudative pleural effusions aids in improved clinical decision making with minimal resources in resource limited settings like ours. SAARC J TUBER LUNG DIS HIV/AIDS, 2017; XIV(1), page: 33-39